1984
DOI: 10.1136/gut.25.9.936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pectin on jejunal glucose absorption and unstirred layer thickness in normal man.

Abstract: SUMMARY The effect of high methoxy apple pectin, a carbohydrate gelling agent, on the intestinal absorption of glucose, water, and sodium was studied in man. The effect of intraluminal fibre was evaluated in 22 healthy volunteers by the intestinal perfusion technique under an occlusive balloon. The test solutions (NaCl 130 mM, KCI 5 mM, glucose or mannitol 30 mM, PEG 4000 5 g/l) were perfused just beyond the ligament of Treitz at a rate of 10 ml/min. A 25 cm segment was studied. Three concentrations of pectin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(68 citation statements)
references
References 16 publications
5
61
1
1
Order By: Relevance
“…However, maximal estimates of unstirred layer thickness in man can be easily obtained from previous reports of glucose absorption from infusates containing low concentrations of glucose (9,10,22,(27)(28)(29)(30)(31). For this calculation, REP was assumed to' be negligible and the area of the luminal aqueous barrier was assumed to have an area equal to a cylinder over the villous tips.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, maximal estimates of unstirred layer thickness in man can be easily obtained from previous reports of glucose absorption from infusates containing low concentrations of glucose (9,10,22,(27)(28)(29)(30)(31). For this calculation, REP was assumed to' be negligible and the area of the luminal aqueous barrier was assumed to have an area equal to a cylinder over the villous tips.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo measurements in rats generally have yielded unstirred layers of at least 300 gm thickness (3,11,(14)(15)(16)(17), and in man and dogs this layer is said to be greater than 600,gm (9,10,12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the increased viscosity of the food obtained with soluble ®bres may further reduce the rate of small intestinal absorption. Indeed an increase in the viscosity of food may have several effects: (a) to slow down the small intestinal transit (Low, 1988;Cherbut et al, 1994); but Cummings et al (1979) did not ®nd any modi®cation of oro-cecal transit time with pectin; (b) to reduce the interaction between food nutrients and digestive enzymes (Flourie  et al, 1984;Cummings et al, 1979; to increase the time for nutrient diffusion, by increasing the thickness of the unstirred water layer (Flourie  et al, 1984;Rydning & Berstad, 1986). This is consistent with the studies which have demonstrated that soluble ®bres could decrease the area under the curve of serum glucose after a duodenal glucose load (Berggren et al, 1993).…”
Section: Inhibition Of Food Intake By Psyllium D Rigaud Et Almentioning
confidence: 99%
“…Cellulose and pectin are known to be poorly absorbable polysaccharides. It has been reported that they suppress increases in plasma glucose concentration and glucose absorption in the small intestine (8,9). We hypothesized that salmon PG may have effects similar to those of cellulose and pectin.…”
mentioning
confidence: 99%